Designing Patient-Centric Information Displays for Hospitals - Wilcox, Lauren; Morris, Dan; Tan, Desney; Gatewood, Justin (Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 2010)
Electronic medical records are increasingly comprehensive, and this vast repository of information has already contributed to medical efficiency and hospital procedure. However, this information is not typically accessible to patients, who are frequently under-informed and unclear about their own hospital courses. In this paper, we propose a design for in-room, patient-centric information displays, based on iterative design with physicians. We use this as the basis for a Wizard-of-Oz study in an emergency department, to assess patient and provider responses to in-room information displays. 18 patients were presented with real-time information displays based on their medical records. Semi-structured interviews with patients, family members, and hospital staff reveal that subjective response to in-room displays was overwhelmingly positive, and through these interviews we elicited guidelines regarding specific information types, privacy, use cases, and information presentation techniques. We describe these findings, and we discuss the feasibility of a fully-automatic implementation of our design.